Course of Hyperkalemia in Patients on Hemodialysis - Bruce Spinowitz; Steven Fishbane; Masafumi Fukagawa; Martin Ford; Nicolas Guzman; Anjay Rastogi (International Journal of Nephrology)
Background. Evidence of longitudinal serum potassium (sK+) concentrations in hyperkalemic hemodialysis patients is sparse. Objective. These post hoc analyses of the placebo arm of the phase 3b DIALIZE study (NCT03303521) explored the course of hyperkalemia in hemodialysis patients receiving placebo. Methods. In DIALIZE, 196 patients receiving hemodialysis three times weekly were randomized to placebo or sodium zirconium cyclosilicate 5 g starting dose once daily on nondialysis days for 8 weeks. In these post hoc analyses of placebo patients overall (n = 86) and by predialysis sK+ subgroups at randomization <5.5 mmol/L, 5.5 to <6.0 mmol/L, 6.0 to <6.5 mmol/L, and ≥6.5 mmol/L, we assessed mean predialysis sK+ concentration by visit and the proportions of patients with mean predialysis sK+ ranges of 4.0–5.0 and 4.0–5.5 mmol/L by visit. Results. In placebo patients, the mean predialysis sK+ concentration at randomization was 5.9 mmol/L, and 5.8 mmol/L at the end of the study (day 57). For placebo patients overall and across all predialysis sK+ subgroups, the mean predialysis sK+ concentration remained ≥5.0 mmol/L for all visits over 8 weeks. Overall, 7–21% and 27–62% of placebo patients had predialysis sK+ ranges of 4.0–5.0 and 4.0–5.5 mmol/L, respectively, at any visit. The proportions of placebo patients with either predialysis sK+ range were greatest for those who were least hyperkalemic (<5.5 mmol/L) and generally decreased with increasing predialysis sK+ concentration. Conclusions. Patients receiving placebo and hemodialysis maintained high predialysis sK+ concentrations over 8 weeks following a hyperkalemic event. Most placebo patients remained hyperkalemic and may be at continued risk of adverse events.